Alcohol use, aquatic injury, and unintentional drowning: A systematic literature review. (3rd June 2018) - Hamilton, Kyra; Keech, Jacob J.; Peden, Amy E.; Hagger, Martin S.
Abstract: Issues: Drowning is a global public health issue, and there is a strong association between alcohol and risk of drowning. No previous systematic review known to date has identified factors associated with alcohol use and engagement in aquatic activities resulting in injury or drowning (fatal and non‐fatal). Approach: Literature published from inception until 31 January 2017 was reviewed. Included articles were divided into three categories: (i) prevalence and/or risk factors for alcohol‐related fatal and non‐fatal drowning and aquatic injury, (ii) understanding alcohol use and aquatic activities, and (iii) prevention strategies. Methodological quality of studies was assessed using National Health and Medical Research Council (NHMRC) Level of Evidence and risk of bias was assessed using the Newcastle‐Ottawa Quality Assessment Scales. Key Findings: In total, 74 studies were included (57 on prevalence and/or risk factors, 15 on understanding alcohol use, and two on prevention strategies). Prevalence rates for alcohol involvement in fatal and non‐fatal drowning varied greatly. Males, boating, not wearing lifejackets, and swimming alone (at night, and at locations without lifeguards) were risk factors for alcohol‐related drowning. No specific age groups were consistently identified as being at risk. Study quality was consistently low, and risk of bias was consistently high across studies. Only two studies evaluated prevention strategies. Implications: There is a need for higher quality studies and behavioural basic and applied research to better understand and change this risky behaviour. Conclusion: On average, 49.46% and 34.87% of fatal and non‐fatal drownings, respectively, involved alcohol, with large variations among studies observed.